2010
DOI: 10.1002/bit.22604
|View full text |Cite
|
Sign up to set email alerts
|

Predictive modeling of non‐viral gene transfer

Abstract: In non-viral gene delivery, the variance of transgenic expression stems from the low number of plasmids successfully transferred. Here, we experimentally determine Lipofectamine- and PEI-mediated exogenous gene expression distributions from single cell time-lapse analysis. Broad Poisson-like distributions of steady state expression are observed for both transfection agents, when used with synchronized cell lines. At the same time, co-transfection analysis with YFP- and CFP-coding plasmids shows that multiple p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 45 publications
2
57
0
Order By: Relevance
“…Co-transfection efficacy and balanced expression of 2 transgenes in vitro has been demonstrated to be highly variable (Schwake et al, 2010), with only a low number of cells positive for both transgenes when using individual plasmids for co-transfection, thus indicating a potential advantage of delivering 2 transgenes via single vector strategies (Kerrigan et al, 2011).…”
Section: Ga Feichtinger Et Al Non-viral Osteoinductive Gene Therapymentioning
confidence: 99%
“…Co-transfection efficacy and balanced expression of 2 transgenes in vitro has been demonstrated to be highly variable (Schwake et al, 2010), with only a low number of cells positive for both transgenes when using individual plasmids for co-transfection, thus indicating a potential advantage of delivering 2 transgenes via single vector strategies (Kerrigan et al, 2011).…”
Section: Ga Feichtinger Et Al Non-viral Osteoinductive Gene Therapymentioning
confidence: 99%
“…Some specialized models also address the spatial distribution and active transport along microtubules [21]. The stochastic nature of in the delivery process has been investigated for nanoparticles [22] and for plasmid DNA [23]. The use of movies for the analysis of single-cell tracking experiments has been reviewed [24].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we showed that quantitative analysis of transfection at the single-cell level makes it possible to analyze the stochastic aspects of transfection quantitatively [23], [44]. The single cell exhibits time courses that are characterized by a distinct delay time before the onset of expression, a phase of GFP increase and finally a steady state level.…”
Section: Introductionmentioning
confidence: 99%
“…For nonviral gene delivery, the kinetic constants (Table I) are reported as averages in trafficking studies in literature [15], [18], [19], [22]- [24], [44], [50]- [57]. To make the simulation model more realistic, random noise is added to the constants by using a 10% standard deviation applying a Gaussian distribution to account for the variability reported in the literature, which is presumably due to a variety of factors including differences in cell culture conditions and packet formulations.…”
Section: Theoretical Aspects Of Modelmentioning
confidence: 99%